Membangun Lingkungan Belajar Yang Berkelanjutan Dan Kreatif Di SMA Swasta Yapim Taruna Stabat - Sihombing, Dame Ifa; Br. Sipayung, Yuli Pambreni; Purba, Christin Geovani; Br. Tarigan, Juleha; Gulo, Nurhayati (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service (PKM) aims to build a sustainable and creative learning environment at SMA Swasta Yapim Taruna Stabat. This program was motivated by the lack of students' creative activities and the dominance of gadget use that inhibits social interaction and innovation in learning. This PKM activity involves various programs, such as entrepreneurship, gadget-free days in class, library cleanliness, and reading corners (literacy corners). The PKM implementation method includes initial observation, preparation of work programs, and implementation of various activities that last for one month. The results of this activity show an increase in student creativity in utilizing available resources, increased awareness of the cleanliness of the school environment, and increased social interaction through literacy and entrepreneurial activities. In conclusion, this PKM activity succeeded in having a positive impact on the learning environment at SMA Swasta Yapim Taruna Stabat. Suggestions for the sustainability of this program are the need for further monitoring and mentoring so that the results achieved can continue to grow and provide long-term benefits for students and schools.